The heart that beats - Gupta, Kashvi (Research and Humanities in Medical Education, 2017)
An intern narrates her encounter with a 19 year old girl recently diagnosed with giant cell myocarditis and shortlisted for a heart transplant. Inspired by the young girl’s eagerness to live despite the looming difficulties inherent in the future of a transplant recipient, she reflects on her own life and comes to an understanding of why heart transplant surgery, despite making people dependent on life-long medication, also, more importantly, gives them another chance at life.